Herd prevalence of bovine brucellosis and analysis of risk factors in cattle in urban and peri-urban areas of the Kampala economic zone, Uganda - Makita, K.; Fèvre, Eric M.; Waiswa, C.; Eisler, M.C.; Thrusfield, M.V.; Welburn, S.C. (Springer, 2011)
Background Human brucellosis has been found to be prevalent in the urban areas of Kampala, the capital city of Uganda. A cross-sectional study was designed to generate precise information on the prevalence of brucellosis in cattle and risk factors for the disease in its urban and peri-urban dairy farming systems. Results The adjusted herd prevalence of brucellosis was 6.5% (11/177, 95% CI: 3.6%-10.0%) and the adjusted individual animal prevalence was 5.0% (21/423, 95% CI: 2.7% - 9.3%) based on diagnosis using commercial kits of the competitive enzyme-linked immunosorbent assay (CELISA) for Brucella abortus antibodies. Mean within-herd prevalence was found to be 25.9% (95% CI: 9.7% - 53.1%) and brucellosis prevalence in an infected herd ranged from 9.1% to 50%. A risk factor could not be identified at the animal level but two risk factors were identified at the herd level: large herd size and history of abortion. The mean number of milking cows in a free-grazing herd (5.0) was significantly larger than a herd with a movement restricted (1.7, p<0.001). Conclusions Vaccination should be targeted at commercial large-scale farms with free-grazing farming to control brucellosis in cattle in and around Kampala city.